2015
DOI: 10.1063/1.4926765
|View full text |Cite
|
Sign up to set email alerts
|

Electronic transitions and band offsets in C60:SubPc and C60:MgPc on MoO3 studied by modulated surface photovoltage spectroscopy

Abstract: Electronic transitions at interfaces between MoO3 layers and organic layers of C60, SubPc, MgPc, and nano-composite layers of SubPc:C60 and MgPc:C60 have been studied by modulated surface photovoltage (SPV) spectroscopy. For all systems, time dependent and modulated SPV signals pointed to dissociation of excitons at the MoO3/organic layer interfaces with a separation of holes towards MoO3. The highest occupied molecular orbital (HOMO)-lowest unoccupied molecular orbital (LUMO) gaps (EHL) of C60, SubPc, and MgP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 37 publications
(38 reference statements)
0
3
0
Order By: Relevance
“…Among them, transition metal oxides, in particular molybdenum oxide (MoO x ), have been widely used due to their deep lying Fermi level and suitable energy alignment with a variety of organic semiconductors. 332–337 In addition, it has been found that MoO x also increases the device stability by suppressing undesirable interfacial reactions at SubPc/C 60 junction. 338 The use of other metal oxides, such as vanadium oxide (V 2 O x ), have also been reported by Jones and co-workers.…”
Section: Subphthalocyaninesmentioning
confidence: 99%
“…Among them, transition metal oxides, in particular molybdenum oxide (MoO x ), have been widely used due to their deep lying Fermi level and suitable energy alignment with a variety of organic semiconductors. 332–337 In addition, it has been found that MoO x also increases the device stability by suppressing undesirable interfacial reactions at SubPc/C 60 junction. 338 The use of other metal oxides, such as vanadium oxide (V 2 O x ), have also been reported by Jones and co-workers.…”
Section: Subphthalocyaninesmentioning
confidence: 99%
“…Defect states near the band edges, or tail states ( E t ), could be quantified by interpreting the slope of the exponentially distributed defect states in the SPV signals originating from the sub‐bandgap‐induced charge separation signals. [ 47 ] Figure a shows spectra of the SPV amplitude on a logarithmic scale for the as‐prepared perovskite deposited on untreated TiO 2 and Li‐treated TiO 2 and for these samples after aging for 1000 h. E t increases to 24 meV for the fresh perovskite and slightly decreases to 23.3 meV for the Li10‐treated sample. By contrast, E t slightly increases with increasing Co content, and these plots are presented in Figure 4b.…”
Section: Resultsmentioning
confidence: 99%
“…These HOMO and LUMO values agree well with those obtained by UPS in our previous study. 29 According to the literature, the work function of ITO is 4.70 eV, 40 and the HOMO/LUMO of CuPc and MoO 3 are 41,42 In OPV devices, aer dissociation of photo-excited excitons in the active-layer, holes transport from CuPc in the active-layer passing the ABL, then reach the ITO anode. The routes for hole collection can be schematically shown in Fig.…”
Section: Resultsmentioning
confidence: 99%